An Investigation into Acoustic Properties of Lightly Needled Estabragh Nonwovens Using the Taguchi Method. Issue 3 (September 2014) - Hassanzadeh, Sanaz; Zarrebini, Mohammad; Hasani, Hossein
Sound pollution has become an important issue that has been addressed by scientists of various disciplines. Control of sound in areas of transport and building industries is of paramount importance. Textiles are widely used as sound insulators. Among the broad spectrum of textiles, nonwoven fabrics due to their technical merits and wide acceptance are extensively used as sound controlling media. In this work, various blends of polypropylene and naturally grown hollow Estabragh fibers were used to prepare sound absorptive nonwoven layers. The fiber blends were fed to a laboratory scale carding machine. Carded webs were lightly needled on a laboratory scale needling machine. Acoustic properties of needled samples were evaluated using the Impedance tube method. The Taguchi method was used to analyze the effective parameters influencing fabric acoustic properties. Results show that the proportion of Estabragh fibers in the blends strongly affects the noise absorption coefficient (NAC). Frequency is the second effective factor and is followed by nonwoven layer mass (areal density) and punch density, respectively. It was concluded that layers comprised of 100% Estabragh fibers achieved the highest value of NAC. The results also pointed to existence of a direct correlation between noise absorption coefficient and the amount of punch density exerted during needling process. It was found that the increase in the amount punch density resulted in higher values of NAC.